Why the Hepatitis B Vaccine is not accomplishing its ultimate target?: A Systematic Review (Bangladesh Journal of Medical Microbiology, 2025)
Background: Hepatitis B remains a critical global health issue, affecting 296 million people with severe liver diseases and high mortality. Regional transmission patterns vary, with perinatal and childhood infections posing chronic risks. Despite expanded vaccination efforts, persistent barriers necessitate continued global initiatives for effective control.Objective: This study explores the underlying reasons hindering the full success of Hepatitis B vaccination programs.Methodology: A comprehensive search across multiple databases to identify relevant studies using specific keywords. Only English-language studies matching the review topic were included, while case reports and non-matching studies were excluded. After screening abstracts and full texts, 17 studies were selected for analysis, while 23 others were excluded for not meeting the inclusion criteria.Results: Of the 17 reviewed studies, 11 were cross-sectional surveys, 2 were qualitative studies, 1 was retrospective, 2 were case-control, and 1 was a randomized controlled trial. Sample sizes ranged from 48 to 1026, with diverse participants across occupations and age groups. Ten key barriers to effective hepatitis B vaccination were identified, varying by region. Around 24% of studies focused on high-risk populations, while three examined vaccine escape mutants, posing a significant challenge. Another three studies highlighted vaccine non-responders, which is estimated at 10% globally. More than 53% of studies linked inadequate immunization to low parental education and lack of vaccine awareness. Cultural barriers and needle phobia appeared in 26%, vaccine cost, and availability in 14%, and healthcare workers' insufficient knowledge in 9%, all contributing to vaccination challenges.Conclusion: Hepatitis B vaccination has reduced infection rates, but low coverage and incomplete dosing remain concerns. Addressing vaccination barriers is crucial for prevention. Despite challenges, global HBV eradication is possible with improved vaccination guidelines and enhanced efforts in screening and immunization. Bangladesh Journal of Medical Microbiology, January 2025;19 (1):76-79